An appeal to every British citizen who loves fair play (leaflet) - Citrine, Walter, 1887-1983 ; Attlee, Clement, 1883-1967 ; Lindsay, H. Scott ; Dallas, George, 1878-1961 ; Middleton, J. S.; Elvin, Herbert Henry
1936-07-18 018b-0065-003 292/946/18b/65(iii)